Effect of heat treatment on the generation of structural defects in LaTaO4 ceramics and their correlation with photoluminescent properties - Gasparotto, G. [UNESP]; Nascimento, N. M. [UNESP]; Cebim, Marco Aurelio [UNESP]; Varela, José Arana [UNESP]; Zaghete, M. A. [UNESP] (Elsevier B.V. Sa, 2011)
The synthesis, structure characterization, as well as luminescence properties of LaTaO4 ceramics were investigated in this study. The materials were prepared through the Pechini method. The characterization techniques, including the X-ray diffraction (XRD) as well as the scanning electron microscopy (SEM) were used to analyze the structure and microstructure, respectively. Details of emissions as a result of the type V-O* (or V-O**) defects were determined using photoluminescence (PL) measurements. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Photoluminescence; LaTaO4; Pechini